Stingy Lake Quadrangle, Minnesota, 1964: 7.5 Minute Series (Topographic) Map - United States Department of the Interior Geological Survey; State of Minnesota, Department of Conservation (Iron Range Research Center, 1964)
Stingy Lake quadrangle topographic map (N4730-W9300/7.5) featuring handwritten notations by Ray Segar in pencil and red ink regarding logging railroad lines and camps in the area between Side Lake and Keewatin. The hand written notations include information on the following, logging camps noted with ‘C’.